Permanenze e innovazioni nell'architettura del MediterraneoMediterranean Architecture between Heritage and Innovation Ricerca, interdisciplinarità e confronto di metodi Research, Interdisciplinary Approach and Comparison of Methods - Germanà, Maria Luisa (Scuole di dottorato, 2011)
The volume offers considerable material for reflection on the subject of Mediterranean Architecture between Heritage and Innovation, demonstrating the wide range of aspects linked to architectural technology, highlighting the flexibility of the disciplinary boundaries with regard to the various meanings that can be applied to the concept of resource. To be read as a continuation of previous Osdotta publications, this allows to trace the current developments in third-level education in a particularly critical moment for the university institution, continuing to emphasize the crucial question of the supply/demand in research, in comparison with other institutions and with the world of production in this sector, in the current scenario dominated by increasingly rapid and incisive transformations. The main challenges to be faced are the quality improvement of PhD courses, through reflection on immediate and long-term results, alongside with clarifying the identity contents of the disciplinary sector.